The Influence of Perceived Value And Team Identification on Purchase Intention Licensed Merchandise Persib Club - Nugraha, Krisna Adhitia; Komaladewi, Rita; Budhyawan, Thomas (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study was to determine the effect of perceived value and team identification on the purchase intention of licensed merchandise for the PERSIB Bandung football club. The measurement model used in this study is a data analysis method using Smart PLS 3.0 software. Partial Least Square (PLS) is a statistical method of Structural Equation Modeling (SEM) based on variance designed to solve multiple regression. This research uses a quantitative approach with a descriptive research type. The data collected is in the form of primary data obtained through distributing questionnaires and secondary data obtained through research journals and scientific books. Data collection techniques use the distribution of Google Forms online. In this study, the population is infinite or infinite, where the number of individuals cannot be known with certainty. The population that is the focus of this research is the Persib Bandung club fans who are spread across various regions in Indonesia. The technique for calculating the minimum number of samples in the SEM model refers to the calculation of Hair et al. (1987), which uses multiplication of the number of indicators multiplied by five so that the minimum total sample used is 120 respondents. The research sample used is Persib Bandung football club fans who have visited the official store. The results of the study show that perceived value and team identification have a positive effect on the community's purchase intention of licensed merchandise for the PERSIB Bandung football club.